STUDI KAJIAN FLOKULASI C. VULGARIS MENGGUNAKAN FLOKULAN BERBASIS SELULOSA DAN PANDANGAN EKONOMI TERKAIT FLOKULASI - NINA JULIANA ROBERTA TURNIP (LP2MTBM MAKARIOZ, 2020)
The aim of this study is to provide directions regarding the potential of cellulose-based natural materials as cationicbiopolymer flocculants and to provide an economic view regarding flocculation. The conclusion from the study is that thesource of cellulose is abundant in nature. However, the limitations of cellulose’s utilization require modifications of thesurface. The production of cationic cellulose flocculants must pay attention to the value of the degree of substitution (DS)because it will affect the solubility properties of cellulose which shows whether or not it is easy to use in solution for theflocculation process. In addition, chemical understanding of the structure of cellulose is important to make modificationsaccording to the needs. From an economic point of view, flocculation is still a superior choice in terms of energyconsumption, especially in large volumes. However, it is important to add the study of operational costs related to flocculants,including raw materials for flocculant production, ease of production of flocculants, dosage and costs of flocculants.